Microbiological studies on Hungrii, Rhujuk/Bastanga and Tsutuocie- Fermented food products of Nagaland, India (Funded Work) - BENDANGNARO JAMIR; CHITTA RANJAN DEB (International Journal of Pharma and Bio Sciences, 2018)
Nagaland is inhabited by diverse tribal communities and it produces varieties of fermented foods, which so far least explored. Fermented food products in Nagaland are still produced from spontaneous and uncontrolled fermentation and thus it results in a product of variable quality. In, this study, the vegetable based fermented food products i.e., Hungrii (Brassica leaves), Rhujuk/Bastanga (Bamboo shoot) and Tsutuocie (Cucumber) have been studied for their microbial population. Microbiological analysis of the fermented products revealed the presence of Bacillus species in almost all the fermented food products. Food contaminant like Staphylococcus was detected in the fermented product, as fermentation in Nagaland is still carried out at the household levels using traditional methods.